Modeling the facet growth rate dispersion of βl-glutamic acid—Combining single crystal experiments with nD particle size distribution data. (8th September 2015) - Ochsenbein, David R.; Schorsch, Stefan; Salvatori, Fabio; Vetter, Thomas; Morari, Manfred; Mazzotti, Marco
Abstract: The growth rate dispersion of needle-like β l -glutamic acid in the length direction is measured using a stagnant solution hot stage microscopy setup. Possible causes of the observed dispersion are analyzed and the resulting distribution of growth rates is used to motivate and reconstruct a distribution of an internal, growth affecting property of the crystals. The latter is then used as the initial condition for a multidimensional, morphological population balance model, whose outputs are fitted to 2D particle size distribution measurements obtained from seeded batch desupersaturation experiments. It is shown, through analysis of both types of data, that a non-zero rate of change in the direction of the new coordinate is required and a phenomenological description of this rate is proposed. The resulting model is able to quantitatively describe experimental data obtained from independent measurement devices, operating at different scales simultaneously. Abstract : Highlights: A hot stage device for the measurement of single crystal morphology is shown. The growth rate dispersion of beta l -glutamic acid is studied. A population balance model for the description of shape and GRD is proposed. The model is fitted to single crystal and population data.